Application of silicon improved rice productivity and reduced chalky rice - Engku Abdullah, Engku Hasmah; Misran, Azizah; Yusop, Mohd Rafii; Yaapar, Muhammad Nazmin; Ramli, Asfaliza (Khon Kaen University,Research and Technology Transfer Affairs Division, 2026)
Chalkiness, together with head rice, is an important indicator of rice appearance quality. Chalky grains are more brittle than translucent grains and tend to break easily during milling. Silicon (Si) is recognized as a beneficial element that supports plant growth and enhances crop performance, particularly in rice. This study investigated the effect of Si application on rice yield, yield components and grain quality, including chalkiness. The available Si content in soil was also quantified. A pot experiment was conducted under a net-house from 2017 to 2018 across two planting cycles using Malaysian rice varieties, MR 263 and MR 297 (officially declared as MARDI Siraj 297). Five Si application rates, which were 0 (Si0), 100 (Si100), 200 (Si200), 300 (Si300), 400 (Si400) kg/ha, were arranged in a randomized complete block design (RCBD) with three replications. Results indicated that Si application significantly increased available Si in the soil, with Si300 and Si400 increased by up to 79.8% compared to the baseline. Yield components, including the number of panicles and percentage of filled grains, increased significantly, resulting in higher rice yield. The optimum Si rate for maximum rice yield (9.10 t/ha) was estimated at 247 kg/ha. Furthermore, Si application increased head rice yield, reduced the percentage of broken rice and chalkiness, and improved grain whiteness. Regardless of variety, chalkiness and broken rice decreased by 55% and 19%, respectively, from Si0 to Si400. In conclusion, Si fertilization effectively improved rice productivity and grain quality, particularly by reducing the percentages of chalkiness and broken rice.